European Citizenship under Stress Social Justice, Brexit and Other Challenges - Cambien, Nathan; Kochenov, Dimitry; Muir, Elise (Nijhoff Studies in European Union Law, 2020)
European citizenship is facing numerous challenges, including fundamental rights and social justice considerations. These get amplified in the context of Brexit and the general rise of populism in Europe today. This book takes a representative selection of these challenges, which raise a multitude of highly complex issues, as an invitation to provide a critical appraisal of the current state of the EU legal framework surrounding EU citizenship. The contributions are grouped in four parts, dealing with constitutional developments posing challenges to EU citizenship; the limits of the free movement paradigm in the context of EU citizenship; EU citizenship beyond free movement; and, lastly, EU citizenship in the context of the outside world, including Brexit, the EEA, and Eurasian Economic Union. Readership: All scholars, advances students and practitioners interested in EU citizenship law in its evolution and broad context could benefit from this book.